Comparison of the Effectiveness of the Successful Intelligence Training Package Focused on Risky Behaviors with the Executive Functioning Improvement Package on the Inclination to Risky Behavior and Family Affinity among Female Middle School Students Engaged in Risky Behaviors - Baramake , Zahra; Fadavi, Mahboubeh Sadat; Yousefi, Zahra (Health Nexus, 2024)
The present study aimed to compare the effectiveness of the Successful Intelligence Training Package focused on risky behaviors (Baramkeh et al., 2024) with the Executive Functioning Improvement Package (Karimi et al., 2023) on the inclination to risky behavior and family affinity among female middle school students engaged in risky behaviors. The research method was a quasi-experimental design with pre-test, post-test, and follow-up phases, involving two experimental groups and one control group. The population consisted of all middle school students engaged in risky behaviors, from which 60 students were purposively selected based on inclusion and exclusion criteria and randomly assigned to two experimental groups and one control group. All subjects were assessed at three stages of the research using research instruments. These tools included the Inclination to Risky Behavior scale (Paki et al., 2020) and Family Affinity (Yousefi, 2022, cited from Karimi et al., 2023). While the control group was on a waiting list, the experimental groups received eight 120-minute sessions of Executive Functioning training and the Successful Intelligence Training Package focused on risky behaviors. Data were analyzed using descriptive statistics (mean and standard deviation) and analysis of variance with repeated measures. The results indicated that both methods were effective on the dependent variables, and except for self-management, there was no significant difference in effectiveness between the two methods, with executive functioning having more effectiveness on the mentioned variable. Based on the findings, it can be said that both training packages are suitable for improving the dependent variables of this research.